SISTEM PENJAMINAN MUTU INTERNAL(SPMI) PADA MADRASAH: SISTEM PENJAMINAN MUTU INTERNAL(SPMI) PADA MADRASAH - , Asy'ari, Sulistyorini_ (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
This article wants to discuss an internal quality assurance system in madrasah. As part of thenational education sub-system, madrasah has the same role in participating in the intellectual lifeof the nation. But madrasah still do not have an internal quality assurance system that is used todevelop quality. The Madrasah Internal Quality Assurance System is a unitary elementconsisting of the organization, policies and processes related to conducting quality assurance ineducation carried out to ensure the realization of quality education that meets or exceeds NationalEducation Standards. As a management system that gives madrasah managers the authority tomanage madrasah by involving stakeholders, the existence of SPMI madrasas is a necessity andis an important part of madrasah-based management with important components in managementare curriculum management, infrastructure, student facilities, financing, and and so on, which isthe task area of the madrasah development team as part of the education quality assurance teamin the Internal Quality Assurance System at the madrasah.Keywords: National Education Standards, madrasah management, Quality Assurance